Corporate Vulnerabilities in Vietnam and Implications of COVID-19. (IMF Working Papers; Working Paper, 2020)
The paper uses firm-level data to assess the financial health of the Vietnamese non-financial corporate sector on the eve of pandemic. Our analysis finds that smaller domestic firms were particularly vulnerable even by regional comparison. A sensitivity analysis suggests that the COVID-19 shock will have a substantial impact on firms' profitability, liquidity and even solvency, particularly in the hardest hit sectors that are dominated by SMEs and account for a sizeable employment share, but large firms are not immune to the crisis. Risks of default can propagate more broadly through upstream and downstream linkages to industries not directly impacted, with stresses potentially translating into an increase in corporate bankruptcies and bank fragility. Policy measures taken in the immediate aftermath of the crisis have helped alleviate liquidity pressures, but the nature of policy support may have to pivot to support the recovery.